Gender analysis and training needs assessment of class 4 staff in a tertiary health care institute - Honavar, Priyanka U.; Samant, Padmaja Y.; Bhosle, Swati B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: A health care team comprises of doctors, nurses, paramedical staff, medical assistants, administrators and support staff or class 4 workers. Each individual has a role in the execution of proper health care delivery to the patients. Obstetrics and gynecology is a dynamic branch requiring urgent attention in most cases right from admission to discharge. Delivery of prompt treatment is possible with better training and coordination of the health care team. In a tertiary care institute, referred patients have more critical health problems and need urgent assistance by well-trained staff. On the other hand, in a smaller set up with less human resource, agile and well-trained support staff would be an asset to overcome the limitations. Better-trained staff means less loss of man-hours from injuries and illnesses, less medico legal liabilities, reduced maintenance cost of equipment and less expenditure on health-related issues of staff. We conducted an interview based cross sectional observational cohort study of the situation and an assessment of needs for skill building of support staff in a tertiary care hospital. At the end, we propose a structured training program suitable to the local needs that can be conducted by experienced peers, technical staff and medical personnel. We studied unmet training needs of the staff and gender related issues. Methods: A questionnaire based cross sectional study involving 92 class 4 workers in the department of obstetrics and gynecology in a tertiary care hospital was conducted comprising questions regarding their demography, work profile, training, needs and problems faced. Key informants in the relevant area were also interviewed. Results: Graphical representation of the responses received has been made. Professional work profile, health issues, gender issues, training need of any specialized training has been highlighted. Conclusions: As an important part of the health care team, this study has brought out issues related to health especially occupational health, needs for training, hurdles faced at work amongst class 4 staff working in the department of obstetrics and gynecology.